Visualization of electrographic flow fields of increasing complexity and detection of simulated sources during spontaneously persistent AF in an animal model - Kong, Melissa H.; Castellano, Steven; Ruppersberg, Peter; Lizama, Ken S.; Avitall, Boaz (Frontiers in Cardiovascular Medicine, 2023)
Atrial fibrillation (AF) is a complex disease that is incompletely understood, so mapping systems have increasingly been employed in attempts to identify its triggers and drivers. Despite these efforts, a recent study found that existing mapping systems were unable to accurately localize pacing sites that served as simulated focal drivers of AF. Electrographic flow (EGF) mapping, analyzed here, allows for near real-time visualization of cardiac conduction patterns across wide portions of an atrium covered by a basket catheter. Through examining a series of maps obtained from animal models in rhythms of increasing complexity, we found that EGF mapping allows for an intuitive understanding of flow patterns that are relatable to underlying anatomy and physiology in a testable and reproducible manner. Additionally, we demonstrate that the guiding metric obtained from mapped triggers of localized AF does not correspond to f wave properties measured from localized electrograms, suggesting that the ability of spectral analysis to provide a deeper understanding of AF propagation may be overstated. These experiments show that EGF mapping can reliably detect pacing sources throughout the atria with high accuracy and without localizing to spurious locations.